LncRNAs-associated to genomic instability: A barrier to cancer therapy effectiveness - Andonegui-Elguera, Marco A; Cáceres-Gutiérrez, Rodrigo E.; Oliva-Rico, Diego; Díaz-Chávez, José; Herrera, Luis A. (Frontiers in Genetics, 2022)
Although a large part of the genome is transcribed, only 1.9% has a protein-coding potential; most of the transcripts are non-coding RNAs such as snRNAs, tRNAs, and rRNAs that participate in mRNA processing and translation. In addition, there are small RNAs with a regulatory role, such as siRNAs, miRNAs, and piRNAs. Finally, the long non-coding RNAs (lncRNAs) are transcripts of more than 200 bp that can positively and negatively regulate gene expression (both in cis and trans), serve as a scaffold for protein recruitment, and control nuclear architecture, among other functions. An essential process regulated by lncRNAs is genome stability. LncRNAs regulate genes associated with DNA repair and chromosome segregation; they are also directly involved in the maintenance of telomeres and have recently been associated with the activity of the centromeres. In cancer, many alterations in lncRNAs have been found to promote genomic instability, which is a hallmark of cancer and is associated with resistance to chemotherapy. In this review, we analyze the most recent findings of lncRNA alterations in cancer, their relevance in genomic instability, and their impact on the resistance of tumor cells to anticancer therapy.